pill box Pengaruh Tingkat Kepatuhan Menggunakan Pill Box Terhadap Keberhasilan Terapi Pasien Hipertensi Di Puskesmas Alalak Tengah - Wahyunita , Sari; Rosyadi , Muhammad Ihsan; Fakhrani , Erwin (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Medication adherence is a crucial factor in the management of hypertension. Non-adherence is a common problem that can hinder therapeutic success. The use of a pill box as a reminder tool is considered to improve adherence; however, its impact on therapeutic outcomes requires further investigation, particularly at Alalak Tengah Primary Health Center, which has a high burden of hypertension cases. Objective: This study aimed to analyze the effect of pill box education on medication adherence and therapeutic success, as well as to examine the relationship between adherence and therapeutic outcomes among hypertensive patients at Alalak Tengah Primary Health Center. Methods: This experimental study with a cross-sectional design employed purposive sampling of 100 uncontrolled hypertensive patients. Data were collected from medical records and pill count observations to measure adherence. Therapeutic success was determined based on achieving target blood pressure. Data analysis was conducted using the Wilcoxon test to compare outcomes before and after the intervention, and the Spearman test to assess the correlation between adherence and therapeutic success. Results: The majority of respondents were female (76%), aged 51–60 years (36.5%), and housewives (71%). The pill box intervention significantly improved therapeutic success, with the proportion of patients achieving target blood pressure increasing from 0% to 79% (p-value = 0.001). Post-intervention medication adherence was very high (97%). However, statistically, there was no significant correlation between adherence and therapeutic success (p-value = 0.636 > 0.05). Conclusion: Education on pill box use was proven effective in significantly improving blood pressure control. However, high medication adherence was not directly correlated with therapeutic success. This indicates that hypertension treatment outcomes are influenced by other multifactorial factors beyond adherence, such as diet, physical activity, and individual responses to medication.